The scholastic experiences of the children of moroccan inmigrants at Centres of Compulsory Secundary Education - Cristóbal Ruiz Román; David Merino Mata (Revista Electrónica Interuniversitaria de Formación del Profesorado)
The following work is the fruit of an investigation was developed in the Department of Educational Theory and History in the University of Málaga, which focus of attention has been to understand the experiences of these adolescents in creating their identity in a series of contexts which, culturally speaking, are extremely diverse: essentially the family, the peer group and school. This article will concentrate on the experiences of the children of Moroccan immigrants in centers of Secondary Education of Málaga and on the expectations, perceptions, difficulties and conflicts that they encounter there.